Effect Of Nitrogen And Sulphur On Their Ratio, Seed Yield And Protein Related Parameters In Developing Soybean (Applied Biological Research, 2015)
The present paper reports the effect of nitrogen and sulphur application  on their ratio, seed yield and protein related parameters in soybean. A  random block design experiment with four treatments [control, nitrogen  (urea @ 31.25 kg N ha-1) and sulphur (gypsum @ 20 kg S ha-1) alone or in  combination] was conducted at PAU, Ludhiana (India) during kharif season 2012 using soybean cultivar ‘SL 525’ as a test crop. Nitrogen and  sulphur alone or in combination significantly increased seed yield and  decreased N:S ratio in the developing soybean leaves, seeds, roots and  stem. Total soluble proteins, free amino acids and S-containing amino  acids (only in leaves) in developing leaves and seeds increased due to  nitrogen and sulphur supply. Results suggested that nitrogen alone causes  maximum protein accumulation and sulphur alone or in combination with  nitrogen maximally increases free amino acids, S-containing amino acids,  seed yield and decreases N:S ratio in soybean.
Keywords: Nitrogen; N:S ratio; protein; soybean; sulphur; yield